Comparison Between Feeding Bloodworms And Artificial Feed On The Rate Of Growth Of Nirwana Fish (Oreochromis Niloticus) In Tanjungsari, West Java - Rosita, Eros; Rostika, Rita; Priowirjanto, Gatot Hari; Grandiosa, Roffi (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2025)
The growth of Nirwana tilapia (Oreochromis niloticus) is strongly influenced by feed and environmental conditions in aquaculture systems. In Indonesia, tilapia productivity is often constrained by feed efficiency and fluctuating water quality. Natural feed such as bloodworms (Chironomus sp.) contains high protein levels that support length growth, while pellets provide complete nutrients for weight gain. This study aimed to evaluate the effects of bloodworms, pellets, and their combination on the growth performance of Nirwana tilapia fingerlings, as well as on water quality (temperature, pH, dissolved oxygen, and ammonia). A Completely Randomized Design (CRD) was applied with three treatments: A (15% bloodworms), B (5% pellets), and C (a combination of 7.5% bloodworms + 2.5% pellets), each with four replications. The fingerlings measured 3–4 cm and were approximately two months old, reared over a period of 50 days. The results showed that all treatments led to increases in weight and length; however, based on analysis of variance (ANOVA), there were no significant differences (p > 0.05) in all growth parameters: weight gain (2.20–2.22 g), length gain (1.32–1.48 cm), specific growth rate (2.41–2.66%/day), daily weight gain (2.73–2.85%/day), and daily length growth (0.0196–0.0210 cm/day). Descriptively, treatment B yielded the highest weight, while treatment A had the highest daily length growth. Water quality remained within optimal ranges (25.5°C temperature, pH 8.2–8.3, DO 4.5–4.7 mg/L, ammonia 0.00–0.01 mg/L). Bloodworms were more effective in stimulating length growth, whereas the feed combination was more efficient in increasing body weight. This study contributes to the development of alternative feed formulations and provides practical recommendations to enhance aquaculture productivity efficiently, sustainably, and in an environmentally friendly manner.